Oxidative stress affects sperm health and fertility—Time to apply facts learned at the bench to help the patient: Lessons for busy clinicians - Pallav Sengupta; Germar‐M. Pinggera; Aldo E. Calogero; Ashok Agarwal (Reproductive Medicine and Biology)
Abstract Background Increased oxidative stress (OS), resulting from the delicate balance between reactive oxygen species (ROS) production and antioxidant defense, is closely linked to sperm abnormalities and male subfertility. Elevated ROS levels particularly affect sperm quality. The vulnerability of spermatozoa to ROS is due to the absence of DNA repair mechanisms and the high presence of polyunsaturated fatty acids in their membranes. Methods This article updates and advances our understanding of the molecular damage caused by OS in spermatozoa, including lipid peroxidation, DNA damage, motility, and functionality. Additionally, the review discusses the challenges in diagnosing OS in semen and recommends accurate and sensitive testing methods. Case studies are utilized to demonstrate the effective management of male infertility caused by OS. Main findings Highlighting the need to bridge the gap between research and clinical practice, this review suggests strategies for clinicians, such as lifestyle and dietary changes and antioxidant therapies. The review emphasizes lifestyle modifications and personalized care as effective strategies in managing male infertility caused by OS. Conclusion This review calls for early detection and intervention and interdisciplinary collaboration to improve patient care in male infertility cases related to increased OS.